Restoring a Healthier Nerve Phenotype: Mechanistic Insights into High-Concentration Capsaicin Topical System (HCCTS) for Painful Diabetic Peripheral Neuropathy (PDPN) - David M. Simpson; Samuel Allen; Audrey Carnevale; Jennifer Lohf (Toxicon, 2026)

Comparing the Impact of the High-Concentration Capsaicin Topical System (HCCTS) on Pain and Sleep in Patients With Painful Diabetic Peripheral Neuropathy (PDPN): Findings from the STEP Randomized Trial and the Real-World CASPAR Study - David M. Simpson; Samuel Allen; Audrey Carnevale; Lizandra Marcondes; Mariëlle Eerdekens (Toxicon, 2026)

First report of Fusarium scirpi causing leaf spot on coconut seedlings in Ghana - Joshua Obeng; Egya Ndede Yankey; Frederick Leo Sossah; Bashiru Adams; Samuel Azupio; Allen Oppong; Joseph Adomako; Esther Afoley Annang; Stephen Larbi-Koranteng; Ophelia Afriyie Obeng; Esther Agyemang Marfo; Owusu Fordjour Aidoo (Crop Protection, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Sustaining Productivity while Reducing Methane Emission in Calcareous Soils: Implications of Combining Inorganic Fertilizer and Biochar - Agbesi Kwadzo Keteku; Isaac Kodzo Amegbor; Stephen Yeboah; Patricia Amankwaa-Yeboah; Richard Dormatey; Kennedy Agyeman; Mavis Badu Brempong; Ernest Baafi; Maxwell Darko Asante; Allen Oppong; Samuel Aduse Poku; Eric Owusu Danquah; et al. (International Journal of Plant Production, 2025)
A considerable proportion of applied nutrients are adsorbed by the calcite surface of calcareous soils, making them unavailable to plants. A combination of organic amendments and fertilizers can improve nutrient retention and mineralization, and also reduce greenhouse gas (GHG) emissions. A two-years field experiment was undertaken to investigate the impacts of inorganic fertilizer, biochar and silicon on nutrient uptake, growth, yield and post-harvest soil chemistry in calcareous soil using rice ( Oryza sativa L.) as a test crop. The implication of each treatment on methane emissions was also investigated. The combination of NPK, biochar and silicon significantly improved rice growth, yield, P and Si uptake; and post-harvest soil nutrition. Biochar increased soil organic carbon content between 4.2 and 108.5% across the years. An increase from 2.4 to 6.1% was observed in the inorganic fertilizer treatments, 11.4–12.0% for the biochar treatments and 2.5–19.0% for ½NPK + biochar from 2020 to 2021. Maximum grain yield was achieved with the treatment ½NPK + biochar + 100 kg Si ha − 1 which was comparable to NPK + 100 kg Si ha − 1 . Also, the combination of ½NPK + biochar + 50 kg Si reduced CH 4 emissions and produced a comparable yield to NPK + 50 kg Si in both years. While further research is required to explore the effects of the length of time biochar is applied on reducing CH 4 emissions, this study suggests a basis for predicting the impact of biochar on the management of CH 4 emissions in calcareous soils.

Demographic History and Adaptive Evolution of Indo‐Pacific Bottlenose Dolphins ( Tursiops aduncus ) in Western Australia - Svenja M. Marfurt; Delphine B. H. Chabanne; Samuel Wittwer; Manuela R. Bizzozzero; Simon J. Allen; Livia Gerber; Krista Nicholson; Michael Krützen (Molecular Ecology, 2024)
Demographic processes can substantially affect a species' response to changing ecological conditions, necessitating the combined consideration of genetic responses to environmental variables and neutral genetic variation. Using a seascape genomics approach combined with population demographic modelling, we explored the interplay of demographic and environmental factors that shaped the current population structure in Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) along the Western Australian coastline. We combined large‐scale environmental data gathered via remote sensing with RADseq genomic data from 133 individuals at 19 sampling sites. Using population genetic and outlier detection analyses, we identified three distinct genetic clusters, coinciding with tropical, subtropical and temperate provincial bioregions. In contrast to previous studies, our demographic models indicated that populations occupying the paleo‐shoreline split into two demographically independent lineages before the last glacial maximum (LGM). A subsequent split after the LGM 12—15 kya gave rise to the Shark Bay population, thereby creating the three currently observed clusters. Although multi‐locus heterozygosity declined from north to south, dolphins from the southernmost cluster inhabiting temperate waters had higher heterozygosity in potentially adaptive loci compared to dolphins from subtropical and tropical waters. These findings suggest ongoing adaptation to cold‐temperate waters in the southernmost cluster, possibly linked to distinct selective pressures between the different bioregions. Our study demonstrated that in the marine realm, without apparent physical boundaries, only a combined approach can fully elucidate the intricate environmental and genetic interactions shaping the evolutionary trajectory of marine mammals.

Meeting the costs of decarbonising industry – The potential effects on prices and competitiveness (a case study of the UK) - Samuel J.G. Cooper; Stephen R. Allen; Ahmed Gailani; Jonathan B. Norman; Anne Owen; John Barrett; Peter Taylor (Energy Policy, 2024)

Targeting mitochondria in the aged cerebral vasculature with SS-31, a proteomic study of brain microvessels - Abigail Seman; Partha K. Chandra; Stephanie D. Byrum; Samuel G. Mackintosh; Allen J. Gies; David W. Busija; Ibolya Rutkai (GeroScience, 2023)
Cognitive impairment and dementias during aging such as Alzheimer’s disease are linked to functional decline and structural alterations of the brain microvasculature. Although mechanisms leading to microvascular changes during aging are not clear, loss of mitochondria, and reduced efficiency of remaining mitochondria appear to play a major role. Pharmacological agents, such as SS-31, which target mitochondria have been shown to be effective during aging and diseases; however, the benefit to mitochondrial- and non-mitochondrial proteins in the brain microvasculature has not been examined. We tested whether attenuation of aging-associated changes in the brain microvascular proteome via targeting mitochondria represents a therapeutic option for the aging brain. We used aged male (> 18 months) C57Bl6/J mice treated with a mitochondria-targeted tetrapeptide, SS-31, or vehicle saline. Cerebral blood flow (CBF) was determined using laser speckle imaging during a 2-week treatment period. Then, isolated cortical microvessels (MVs) composed of end arterioles, capillaries, and venules were used for Orbitrap Eclipse Tribrid mass spectrometry. CBF was similar among the groups, whereas bioinformatic analysis revealed substantial differences in protein abundance of cortical MVs between SS-31 and vehicle. We identified 6267 proteins, of which 12% were mitochondria-associated. Of this 12%, 107 were significantly differentially expressed and were associated with oxidative phosphorylation, metabolism, the antioxidant defense system, or mitochondrial dynamics. Administration of SS-31 affected many non-mitochondrial proteins. Our findings suggest that mitochondria in the microvasculature represent a therapeutic target in the aging brain, and widespread changes in the proteome may underlie the rejuvenating actions of SS-31 in aging.

Reconstructing the colonization history of Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) in Northwestern Australia - Samuel Wittwer; Livia Gerber; Simon J. Allen; Erik P. Willems; Svenja M. Marfurt; Michael Krützen (Molecular Ecology, 2023)
Bottlenose dolphins ( Tursiops spp.) are found in waters around Australia, with T. truncatus typically occupying deeper, more oceanic habitat, while T. aduncus occur in shallower, coastal waters. Little is known about the colonization history of T. aduncus along the Western Australian coastline; however, it has been hypothesized that extant populations are the result of an expansion along the coastline originating from a source in the north of Australia. To investigate the history of coastal T. aduncus populations in the area, we generated a genomic SNP dataset using a double‐digest restriction‐site‐associated DNA (ddRAD) sequencing approach. The resulting dataset consisted of 103,201 biallelic SNPs for 112 individuals which were sampled from eleven coastal and two offshore sites between Shark Bay and Cygnet Bay, Western Australia. Our population genomic analyses showed a pattern consistent with the proposed source in the north with significant isolation by distance along the coastline, as well as a reduction in genomic diversity measures along the coastline with Shark Bay showing the most pronounced reduction. Our demographic analysis indicated that the expansion of T. aduncus along the coastline began around the last glacial maximum and progressed southwards with the Shark Bay population being founded only 13 kya. Our results are in line with coastal colonization histories inferred for Tursiops globally, highlighting the ability of delphinids to rapidly colonize novel coastal niches as habitat is released during glacial cycle‐related global sea level and temperature changes.

Passive acoustic feeders as a tool to assess feed response and growth in shrimp pond production - João Reis; Aya S. Hussain; Alexis Weldon; Samuel Walsh; William Stites; Melanie Rhodes; D. Allen Davis (Aquaculture International, 2023)

Effects of concurrent exercise training on body composition, systemic inflammation, and components of metabolic syndrome in inactive academics: a randomised controlled trial - Samuel M. Higham; Amy E. Mendham; Simon Rosenbaum; Nicholas G. Allen; Greg Smith; Antony Stadnyk; Rob Duffield (European Journal of Applied Physiology, 2023)

Reproductive ecology of muskellunge ( Esox masquinongy ), an introduced predator, in the lower Wolastoq/Saint John River, New Brunswick, Canada - Kaleb Zelman; Phillip Harrison; Antóin M. O'Sullivan; Samuel Andrews; Stephen Peake; Tommi Linnansaari; Scott A. Pavey; R. Allen Curry (Journal of Fish Biology, 2023)
Introduced predators can have harmful top‐down effects on their newly colonized system through competition with and direct predation on native species. Following an initial introduction of muskellunge in Lac Frontière, Québec in the 1970s at the headwaters of the Wolastoq/Saint John River, the species rapidly migrated downstream, expanding its range by ~500 km over ~20 years. Despite this expansive colonization and concern over possible threats to native species, little is known about the basic ecology of muskellunge in this system. The last downstream barrier is the hydroelectric facility, Mactaquac Generating Station (MGS), 150 km upstream of the sea. While there are no downstream fish passage facilities at MGS, adult muskellunge have been recorded downstream. In this study, muskellunge ( n = 23) were surgically tagged with very‐high‐frequency (VHF) radio or combined acoustic radio telemetry (CART) tags and tracked over two spawning seasons. We sought to determine if there was a reproducing population downstream of MGS and tracked Tagged muskellunge over two spawning seasons. We tracked fish to locate and confirm spawning sites, and followed up with egg and/or juvenile sampling surveys. Tagged muskellunge (90%) moved upstream towards the MGS during the spawning period in each year (2016 and 2017), where they remained throughout the entire spawning period. No spawning or nursery sites were confirmed near MGS, but in 2016 three distinct spawning locations and six distinct nursery sites were confirmed 10–12 km downstream amongst a chain of flooded islands. In 2016, eggs, sac‐fry and juveniles were collected and confirmed as muskellunge by genetic sequencing, providing the first empirical observation of successful spawning downstream of MGS.

Toxicity comparison of atrazine on Eisenia fetida in artificial soil and three natural soils - Xiaoying Li; Yue Yang; Ruolin Wu; Kaixuan Hou; Samuel C. Allen; Lusheng Zhu; Zhongkun Du; Bing Li; Jinhua Wang; Jun Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Global drivers of historical true fruit fly (Diptera: Tephritidae) invasions - Jiří Trombik; Samuel F. Ward; Allen L. Norrbom; Andrew M. Liebhold (Journal of Pest Science, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Association patterns and community structure among female bottlenose dolphins: environmental, genetic and cultural factors - Svenja M. Marfurt; Simon J. Allen; Manuela R. Bizzozzero; Erik P. Willems; Stephanie L. King; Richard C. Connor; Anna M. Kopps; Sonja Wild; Livia Gerber; Samuel Wittwer; Michael Krützen (Mammalian Biology, 2022)
Social structuring from assortative associations may affect individual fitness, as well as population-level processes. Gaining a broader understanding of social structure can improve our knowledge of social evolution and inform wildlife conservation. We investigated association patterns and community structure of female Indo-Pacific bottlenose dolphins ( Tursiops aduncus ) in Shark Bay, Western Australia, assessing the role of kinship, shared culturally transmitted foraging techniques, and habitat similarity based on water depth. Our results indicated that associations are influenced by a combination of uni- and biparental relatedness, cultural behaviour and habitat similarity, as these were positively correlated with a measure of dyadic association. These findings were matched in a community level analysis. Members of the same communities overwhelmingly shared the same habitat and foraging techniques, demonstrating a strong homophilic tendency. Both uni- and biparental relatedness between dyads were higher within than between communities. Our results illustrate that intraspecific variation in sociality in bottlenose dolphins is influenced by a complex combination of genetic, cultural, and environmental aspects.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

Evaluation of the Penman-Monteith and other 34 reference evapotranspiration equations under limited data in a semiarid dry climate - Koffi Djaman; Michael O’Neill; Lamine Diop; Ansoumana Bodian; Samuel Allen; Komlan Koudahe; Kevin Lombard (Theoretical and Applied Climatology, 2019)

Impact of Future Climate Change on Water Temperature and Thermal Habitat for Keystone Fishes in the Lower Saint John River, Canada - Stephen J. Dugdale; R. Allen Curry; André St-Hilaire; Samuel N. Andrews (Water Resources Management, 2018)

The effect of high-intensity aerobic interval training on markers of systemic inflammation in sedentary populations - Nicholas G. Allen; Samuel M. Higham; Amy E. Mendham; Tegan E. Kastelein; Penelope S. Larsen; Rob Duffield (European Journal of Applied Physiology, 2017)

Effort rights‐based management - Dale Squires; Mark Maunder; Robin Allen; Peder Andersen; Kepa Astorkiza; Douglas Butterworth; Gonzalo Caballero; Raymond Clarke; Hans Ellefsen; Patrice Guillotreau; John Hampton; Rögnvaldur Hannesson; et al. (Fish and Fisheries, 2017)
Effort rights‐based fisheries management ( RBM ) is less widely used than catch rights, whether for groups or individuals. Because RBM on catch or effort necessarily requires a total allowable catch ( TAC ) or total allowable effort ( TAE ), RBM is discussed in conjunction with issues in assessing fish populations and providing TAC s or TAE s. Both approaches have advantages and disadvantages, and there are trade‐offs between the two approaches. In a narrow economic sense, catch rights are superior because of the type of incentives created, but once the costs of research to improve stock assessments and the associated risks of determining the TAC and costs of monitoring, control, surveillance and enforcement are taken into consideration, the choice between catch or effort RBM becomes more complex and less clear. The results will be case specific. Hybrid systems based on both catch and effort are increasingly employed to manage marine fisheries to capture the advantages of both approaches. In hybrid systems, catch or effort RBM dominates and controls on the other supplements. RBM using either catch or effort by itself addresses only the target species stock externality and not the remaining externalities associated with by‐catch and the ecosystem.

Temporal variability in aboveground plant biomass decreases as spatial variability increases - Devan Allen McGranahan; Torre J. Hovick; R. Dwayne Elmore; David M. Engle; Samuel D. Fuhlendorf; Stephen L. Winter; James R. Miller; Diane M. Debinski (Ecology, 2016)
Ecological theory predicts that diversity decreases variability in ecosystem function. We predict that, at the landscape scale, spatial variability created by a mosaic of contrasting patches that differ in time since disturbance will decrease temporal variability in aboveground plant biomass. Using data from a multi‐year study of seven grazed tallgrass prairie landscapes, each experimentally managed for one to eight patches, we show that increased spatial variability driven by spatially patchy fire and herbivory reduces temporal variability in aboveground plant biomass. This pattern is associated with statistical evidence for the portfolio effect and a positive relationship between temporal variability and functional group synchrony as predicted by metacommunity variability theory. As disturbance from fire and grazing interact to create a shifting mosaic of spatially heterogeneous patches within a landscape, temporal variability in aboveground plant biomass can be dampened. These results suggest that spatially heterogeneous disturbance regimes contribute to a portfolio of ecosystem functions provided by biodiversity, including wildlife habitat, fuel, and forage. We discuss how spatial patterns of disturbance drive variability within and among patches.

Mapping the distribution of maize streak virus genotypes across the forest and transition zones of Ghana - Allen Oppong; Samuel K. Offei; Kwadwo Ofori; Hans Adu-Dapaah; Joseph N. L. Lamptey; Brigitta Kurenbach; Matthew Walters; Dionne N. Shepherd; Darren P. Martin; Arvind Varsani (Archives of Virology, 2015)

Angiogenesis and airway reactivity in asthmatic Brown Norway rats - Elizabeth M. Wagner; John Jenkins; Anne Schmieder; Lindsey Eldridge; Qiong Zhang; Aigul Moldobaeva; Huiying Zhang; John S. Allen; Xiaoxia Yang; Wayne Mitzner; Jochen Keupp; Shelton D. Caruthers; et al. (Angiogenesis, 2015)

Hybrid poplar (Populus spp.) adaptation to a semi-arid region: results from Northwest New Mexico (2002–2011) - Michael K. O’Neill; Samuel C. Allen; Robert F. Heyduck; Kevin A. Lombard; Dan Smeal; Richard N. Arnold (Agroforestry Systems, 2014)

The Cascadia Initiative: A Sea Change In Seismological Studies of Subduction Zones - Douglas Toomey; Richard Allen; Andrew Barclay; Samuel Bell; Peter Bromirski; Richard Carlson; Xiaowei Chen; John Collins; Robert Dziak; Brent Evers; Donald Forsyth; Peter Gerstoft; et al. (Oceanography, 2014)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

Agroforestry Today: An Analysis of the 750 Presentations to the 1st World Congress of Agroforestry, 2004 - P.K. Ramachandran Nair; Samuel C. Allen; Michael E. Bannister (Journal of Forestry, 2005)
The developmental stage of a discipline can be gauged by the nature of its publications. Major themes of the 750 presentations at the 1st World Congress of Agroforestry, Orlando, Florida, 2004, were biological and ecological (28%); communication and knowledge integration (24%); and economics, marketing, and social issues (23%). The presentations related mostly (88% of total) to the tropics. About 55% of the authors came from educational institutions, 21% represented governments, and 13% represented nongovernmental organizations. The presentations showed that sustainability continued to be a major conceptual foundation of agroforestry, but there was considerable tropical-temperate contrast in efforts to attain sustainability. Although issues such as poverty alleviation, food security, and attainment of the Millennium Development Goals dominate the research and development agenda in the tropics, the focus in the temperate region is on environmental services such as carbon sequestration, water quality enhancement, and biodiversity conservation. The nature, diversity, and distribution of presentations as well as the current trends in agroforestry research suggest that agroforestry is maturing as a robust discipline.

Nitrogen mineralization in a pecan (Carya illinoensis K. Koch)?cotton (Gossypium hirsutum L.) alley cropping system in the southern United States - Samuel C. Allen; Shibu Jose; P. K. R. Nair; Barry J. Brecke; Vimala D. Nair; Donald A. Graetz; Craig L. Ramsey (Biology and Fertility of Soils, 2005)

Competition for 15N-labeled fertilizer in a pecan (Carya illinoensis K. Koch)-cotton (Gossypium hirsutum L.) alley cropping system in the southern United States - Samuel C. Allen; Shibu Jose; P.K.R. Nair; Barry J. Brecke; Craig L. Ramsey (Plant and Soil, 2004)

Interaction of Differently Designed Immunoliposomes with Colon Cancer Cells and Kupffer Cells. An in Vitro Comparison - Gerben A. Koning; Henriëtte W. M. Morselt; Arko Gorter; Theresa M. Allen; Samuel Zalipsky; Gerrit L. Scherphof; Jan A. A. M. Kamps (Pharmaceutical Research, 2003)

Pharmacokinetics of Differently Designed Immunoliposome Formulations in Rats with Or Without Hepatic Colon Cancer Metastases - Gerben A. Koning; Henriëtte W. M. Morselt; Arko Gorter; Theresa M. Allen; Samuel Zalipsky; Jan A. A. M. Kamps; Gerrit L. Scherphof (Pharmaceutical Research, 2001)

Left Ventricular Contractility is Impaired Following Myocardial Infarction in the Pig and Rat: Assessment by the End Systolic Pressure–Volume Relation Using a Single-Beat Estimation Technique and Cine Magnetic Resonance Imaging - Randy Setser; Robert E. Henson II; J. Stacy Allen; Stefan E. Fischer; Samuel A. Wickline; Christine H. Lorenz (Annals of Biomedical Engineering, 2000)